ANALISIS KEBIJAKAN DALAM STRUKTUR ORGANISASI SEKRETARIATAN DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN BADUNG - Sunu, Ida Bagus Gede Bayu; Erviantono, Tedi; Mertha, A.A.S. Mirah Mahaswari Jayanthi (Jurnal Nawala Politika, 2023)
This research was conducted to analyze the Secretariat Organization of the Badung Regency DPRD based on policy analysis. The researcher hopes that through this research it will be possible to find out how the Secretariat Organization of the Badung Regency DPRD achieves its goals based on policy analysis. Does the performance carried out by the Secretariat Organization at the Badung Regency DPRD refer to the goals to be achieved? The research method used in this study is a qualitative research methodology. The results of this study indicate that the organizational structure of the Badung Regency DPRD secretariat has the authority to make policies based on their respective scope of work and still refers to the main objectives of the secretariat structure of the Badung Regency DPRD itself. Keywords: DPRD Secretariat, Organizational Structure, Policy